Production and Quality Evaluation of Extruded Full-Fat Soy Flour (Biological Sciences - PJSIR, 2006)
Full-fat soy flour was prepared for human consumption by using extrusion technology. Various process param- eters such as feed rate, grain size, moisture content of the ingredients, cooking time, temperature, and speed of the extruder cooker were standardized. The samples of raw soy flour and extruded full-fat soy flour were evaluated by chemical analysis, biological assays, organoleptic evaluation, microbiological analysis and storage stability. Soy flour prepared by extrusion cooking with 22 % moisture content at 138 ºC temperature was in the form of creamy white flakes, which had a good taste, flavour, and nutritive value. These flakes remained stable daring the storage period of 10 months.